2019
DOI: 10.1155/2019/7085104
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Analysis of Settlement Parameters for Postgrouting Piles in Loess Area of Shaanxi, China

Abstract: The settlement calculation of postgrouting piles is complex and depends on the calculation method and parameters. Static load tests were conducted to compare the settlement characteristics of nongrouting and postgrouting piles, and three vital parameters in the layer-wise summation method were revised to predict the settlement of postgrouting piles. The elastic compression coefficient was deduced based on the Mindlin–Geddes method by considering the influence of the change in the pile side resistance distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…Studies have shown that the sawtooth depth "h" has a greater impact on the interfacial (1) Spray watering (2) Insulate high-temperature surrounding rock and add 0.03% high efficiency airentraining agent to spray concrete (3) For the digging puddles in the high-water temperature section, the water pump is used to discharge the hot water (4) Transporting ice cubes to the excavation surface cohesion, and the rough rock surface affects the mechanical behaviour of the concrete (Figure 15). However, there is no quantitative discussion of the effect of roughness on the interface bearing capacity [71,74,75]. Roughness, as an indicator of rock mechanics, plays an important role in studying the mechanical properties of rock contact surface, and it mainly controls the degree of undulation of the contact surface, which in turn affects the shear bite force and frictional resistance [76][77][78][79][80][81].…”
Section: Other Methodsmentioning
confidence: 99%
“…Studies have shown that the sawtooth depth "h" has a greater impact on the interfacial (1) Spray watering (2) Insulate high-temperature surrounding rock and add 0.03% high efficiency airentraining agent to spray concrete (3) For the digging puddles in the high-water temperature section, the water pump is used to discharge the hot water (4) Transporting ice cubes to the excavation surface cohesion, and the rough rock surface affects the mechanical behaviour of the concrete (Figure 15). However, there is no quantitative discussion of the effect of roughness on the interface bearing capacity [71,74,75]. Roughness, as an indicator of rock mechanics, plays an important role in studying the mechanical properties of rock contact surface, and it mainly controls the degree of undulation of the contact surface, which in turn affects the shear bite force and frictional resistance [76][77][78][79][80][81].…”
Section: Other Methodsmentioning
confidence: 99%
“…To compare numerical simulation results with the field measurement results, as well as to more fully understand the vibration characteristic of the tower main frame under the blasting, a three-dimensional finite element model was established by Midas-GTS finite element software, which was generally used to conduct the geotechnical analysis. Based on St. Venant principle [49,50], it is appropriate to take three times of the size of tunnel face for left, right, and bottom parts of the model to reduce the influence of boundary effects. So, the model size is 150 m × 120 m × 90 m, as shown in Figure 12.…”
Section: Numerical Simulation and Analysismentioning
confidence: 99%
“…e dynamic stability of slopes is an important topic in geotechnical engineering [11]. e study of slope dynamic response law is the foundation of slope dynamic stability analysis, including responses of acceleration, velocity, displacement, and stress-strain equivalents [12,13]. Accurate understanding of the dynamic response characteristics of slopes under seismic loads can provide scientific and theoretical guidance for seismic designs in slope engineering.…”
Section: Introductionmentioning
confidence: 99%